Social responsibility and business - Ferrell, O. C.; Thorne, Debbie M.; Ferrell, Linda (Andover : Cengage Learning, 2012)
In this text, we demonstrate and help the instructor prove that social responsibility is a theoretically grounded yet highly actionable and practical field of interest.
Social responsibility framework -- Strategic management of stakeholder relationships -- Corporate governance -- Legal, regulatory, and political issues -- Business ethics and ethical decision making -- Strategic approaches to improving ethical behavior -- Employee relations -- Consumer relations -- Community relations and strategic philanthropy -- Technology issues -- Sustainability issues -- Social responsibility in a global environment
Includes index.
Keywords: BUSINESS ETHICS; SOCIAL RESPONSIBILITY OF BUSINESS